Star of the Show : Magic Puppy #4 - Bentley, Sue, 1951-; Swan, Angela (New York : Grosset & Dunlap, 2009)
Acting in a film for the first time, Tessa is lonely until she meets a magic puppy who helps her make friends and meet her favorite actor.
Tessa, who is acting in a film for the first time, is lonely until she meets a magic puppy who helps her make friends and meet her favorite actor.
Keywords: Motion pictures -- Production and direction -- Fiction; Actors and actresses -- Fiction; Dogs -- Fiction; Magic -- Fiction; Motion pictures -- Production and direction -- Fiction; Actors -- Fiction; Dogs -- Fiction; Magic -- Fiction